(3GdefJbi ef cJGH GdQgHGfs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s
(3ChdgG (B:s
(3Yf hgH Hf efHg bGd (B: (3eQ QLd HQGgH ai Hfi ESQGFjd abGd (B: (3jGQGgH cja PcQc ddehJ bGd eG CQaY bOekG hdG CVY CNQi MJi CQi Cfi ejJ s
(3BNQgG (B:s
(3YHO Gddg Hf bjS jbhd bGd Ydj QVj Gddg Yfg ai gPg GdBjI bQC (B( (3gd ffHFce HGdCNSQjf CYeGdG(B) (3bGd (B: (3ge GdQgHGf GdPjf MHShG CfaSge ai GdShGQi Je GdefJbG ef cJGH GdQgHGf s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3EfJbGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
Keywords: (3GdJUha hGdBOGH GdTQYjIs